Congenital Lateral Palatal Synechia Associated With Cleft Palate: A Case Report With Long-Term Follow-Up and Review of the Literature. (June 2020) - Imai, Yoshimichi; Tachi, Masahiro
Lateral palatal synechiae are rare congenital adhesions running from the free borders of the cleft palate to the lateral parts of the tongue or the oral cavity floor, typically found in cleft palate lateral synechiae syndrome. We present a case of congenital lateral palatal synechia associated with a cleft palate that we treated and followed up for 10 years. We present the long-term prognosis. We also discuss variations in intraoral synechiae associated with cleft palate and the etiology of lateral palatal synechiae through a literature review.